2004
DOI: 10.1177/1524838004269488
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Intimate Partner Violence in the U.S. General Population

Abstract: This article reviews cross-sectional and longitudinal research on ethnic differences related to intimate partner violence (IPV) in the U.S. general population and the role of alcohol use and socioeconomic characteristics. Evidence indicates that significant ethnic differences exist in the prevalence of IPV. Although ethnic minorities report higher rates of IPV, differences in crude rates are reduced after controlling for socioeconomic circumstances and alcohol use. However, Black couples appear to be at greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
111
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 30 publications
8
111
3
2
Order By: Relevance
“…However, there is very little research investigating ways in which BIPs may better address the particular structural, cultural, and contextual issues that lead to IPV in ethnic and racial minority groups. Although some research indicates no difference between racial and ethnic minority groups concerning IPV perpetration (Buttell, Powers, & Wang, 2012;Field & Caetano, 2004;Lipsky, Caetano, & Roy-Byrne, 2009;Rennison & Planty, 2003), most research on the topic highlights race and ethnicity as indicators of IPV (Caetano, Ramisetty-Mikler, & Field, 2005;Melander, Noel, & Tyler, 2010;West, 2012). Culturally focused BIP curricula have received mixed reviews concerning their effectiveness (Gelles, 2001;Gondolf & Williams, 2001;Almeida, Woods, Messineo, & Font, 1998); however, more research should be conducted identifying beneficial cultural factors for integrating into curricula, and more studies should be directed toward the evaluation of these culturally centered programs.…”
Section: Summary Regarding Interventions For Female Perpetratorsmentioning
confidence: 99%
“…However, there is very little research investigating ways in which BIPs may better address the particular structural, cultural, and contextual issues that lead to IPV in ethnic and racial minority groups. Although some research indicates no difference between racial and ethnic minority groups concerning IPV perpetration (Buttell, Powers, & Wang, 2012;Field & Caetano, 2004;Lipsky, Caetano, & Roy-Byrne, 2009;Rennison & Planty, 2003), most research on the topic highlights race and ethnicity as indicators of IPV (Caetano, Ramisetty-Mikler, & Field, 2005;Melander, Noel, & Tyler, 2010;West, 2012). Culturally focused BIP curricula have received mixed reviews concerning their effectiveness (Gelles, 2001;Gondolf & Williams, 2001;Almeida, Woods, Messineo, & Font, 1998); however, more research should be conducted identifying beneficial cultural factors for integrating into curricula, and more studies should be directed toward the evaluation of these culturally centered programs.…”
Section: Summary Regarding Interventions For Female Perpetratorsmentioning
confidence: 99%
“…Results from the 1995 National Study of Couples indicate that almost half of IPV events are mutual , although women are more likely than men to sustain injuries (Archer, 2000). General population samples show that IPV prevalence is highest among younger couples, racial/ ethnic minorities, and couples with objective and subjective household indicators of lower socioeconomic status, including lower income, fi nancial distress, lower education, and unemployment (Bachman and Saltzman, 1995;Field and Caetano, 2004). These indicators often characterize bluecollar couples.…”
mentioning
confidence: 99%
“…Torres (1991) found that Hispanic women tended to endure battering for a longer time than Anglo and African-American women, and Mexican American women, more than Anglo women, tended to view some forms of domestic violence as normal and acceptable. In addition, Field and Caetano (2004) found that when the variables of urbanity, income, employment, and occupation status were controlled, Hispanics still demonstrated a higher prevalence of domestic violence against women than Anglos. Some researchers suggest that the subculture of violence and structural inequality theories may be supplementary rather than contradictory (Raj and Silverman 2002).…”
mentioning
confidence: 95%
“…Families with a lower socio-economic status experience increased stress, because their stressors are more numerous and severe, and they have fewer resources available to cope with these stressors. Stress caused by structural factors may lead to increased frustration, disharmony in interpersonal relationships, and violence (Field and Caetano 2004).…”
mentioning
confidence: 99%